Perancangan Belt Conveyor Dengan Kapasitas Angkut 6 Ton/Jam Pada Pabrik Karet - Antonius FA Silaen; CHAIDIR CHAIDIR (UNIVERSITAS PROF. DR. HAZAIRIN, SH BENGKULU, 2021)
Conveyor belt planning with a capacity of 6 tonnes / hour with a carrying distance of 12m and a slope angle of 200 for a rubber factory. The belt serves as a medium for transporting rubber raw materials, where the planned belt width is (L = 800mm) and the overall length (Ls = 24m) Where the conveyor belt is driven by a pulley whose width is 900 mm, the diameter of the pulley is (Dp = 625 mm), the driving pulley rotation (n = 24.45 rpm), the electric motor as the initial drive for moving the conveyor belt machine to move the pully is used a motor with torsional moment (T = 12906 kg / m), where the shaft material is taken from JlS steel. G. 4501. S. 45. C. Tensile stress 58 kg / mm2. Roll diameter (D = 108), the bearings used are closed type ball bearings with bearing number (6008), inner diameter (d = 40 mm), outer diameter (D = 68 mm), bearing width (B = 15 mm), Specific dynamic nominal capacity (C = 1310 kg), static nominal capacity (Co = 1010 kg).